A CD36-based prediction model for sepsis-induced myocardial injury - Yun Xie; Hui Lv; Daonan Chen; Peijie Huang; Zhigang Zhou; Ruilan Wang (International Journal of Cardiology: Heart & Vasculature)
Background: Sepsis-induced myocardial injury (SIMI) is a prevalent form of organ dysfunction with a significant impact on the mortality rate among sepsis patients. This study aims to develop a predictive model for SIMI using plasma CD36 levels. Methods: A prospective study was conducted from January 1, 2023, to December 1, 2023, involving sepsis patients admitted to the Department of Intensive Care Medicine at Shanghai General Hospital. Plasma CD36 levels were measured within 48 h of ICU admission, prior to the diagnosis of sepsis-associated myocardial injury. Myocardial damage was assessed using troponin levels. Results: Two significant risk factors for SIMI were identified: age and elevated CD36 levels. CD36, THBS1, and BNP were determined to be independent mortality risk factors. The myocardial injury group exhibited higher plasma CD36 levels compared to the non-injury group. Additionally, the deceased group had higher plasma CD36 levels than the survivors. No significant differences in CD36 levels were observed between groups with lung and stomach infections or between Gram-positive and Gram-negative infection groups. Similarly, there was no statistically significant difference in CD36 levels between surgical and medical patients. A predictive model for SIMI was formulated as follows: ln [P/(1-P)] = -0.000818age + 0.4975756CD36 − 5.400293. The model’s quality of fit was tested with a P-value of 0.4682, indicating a good degree of discrimination and calibration, as evidenced by the area under the ROC curve (0.7724). Conclusion: The prognosis of individuals with sepsis is closely associated with elevated CD36 levels. Elevated CD36 is identified as an independent risk factor for both SIMI and mortality in sepsis patients. The predictive model suggests that high CD36 levels are indicative of SIMI and are associated with a poor prognosis.